Kritik Sastra Ekologis terhadap Novel-novel Terbaru Indonesia - Andriyani, Noni; Piliang, Wilda Srihastuty Handayani (GERAM: Gerakan Aktif Menulis, 2019)
Environmental literary works appear as a form of literary sensitivity to society and the environment which has specific environmental tendencies. Studies using the theory of ecological literature began in around 2008 and above with a very limited number. Therefore, the development of studies of literary works with this theory is very necessary. The creation of public opinion about the importance of protecting the environment to reduce the impact of global warming is very necessary. Later, through several novels, authors have done it. However, not all messages in the novel are clearly conveyed so that they still need ecological literary criticism to understand them. Based on this, the problem raised in this study is "What is the ecological literary criticism of Indonesia's latest novels?". Data collection and data analysis is done by descriptive and content analysis methods. Data are classified and analyzed with ecological literary concepts according to Garrard including (1) pollution; (2) wilderness; (3) disaster; (4) housing / residence; (5) animals; and (6) earth. The research findings and discussion show that Indonesia's latest novels are friendly with their environment, want to describe as much detail as possible about the universe, worship nature, and are always interested in natural changes. Ecological literary concepts are contained in Indonesia's latest novels to describe the natural situation as well as to criticize human treatment of nature. Indonesia's latest novels teach that an attitude of compassion for nature gives rise to desire and behavior to protect and preserve nature as well as possible.